Suitability of hearing aids used by students of Sekolah Rendah Pendidikan Khas Jalan Peel, Kuala Lumpur - Ismail, Noraidah (UKM, 1998)
A study was carried out to evaluate the hearing aid fitting among 42 students of Sekolah Rendah Pendidikan Khas Jalan Peel, Kuala Lumpur. The suitability of the fitting was measured by comparing the measured aided thresholds (MAT) and the required aided thresholds (RAT), calculated using the NAL-RP prescriptive formula. Results showed that in all subjects tested, the hearing aids used were not appropriate for their hearing losses in which, 80% of the hearing aids provided under-amplification while over amplification was found in the remaining 20%. Paired t-test indicated that the differences between the MAT and the RAT were very significant (p<0.01) at all tested frequencies. The result of this study revealed a high incidence (100%) of inappropriate hearing aid fitting amongst the tested subjects.